A look through the rear view mirror: Developmental experiences and insights of high performance athletes - Gulbin, J. P.; Oldenziel, K. E.; Weissensteiner, J. R.; Gagne, F. (Talent Development & Excellence, 2010)
This paper chronicles the key developmental experiences and insights of 673 high performance Australian athletes (including 51 Olympians), across 34 sports. A customised survey was developed around Gagne.s (2009) holistic model of talent development which enabled athletes to report in a contextually relevant way. Key thematic variables demonstrated that high performance athletes are characterised by diverse and high level sports participation prior to specialisation, a vast investment and commitment to practice, access to high quality coaching, substantial parental support, an early and enduring passion for sport, and resilience to overcome and bounce back from any obstacles. These factors are contrasted at each of the junior and senior competition development milestones, with theoretical and practical implications specific to athlete and national talent identification system development discussed.